Online Voting of Small and Medium Shareholders, Stock Price Idiosyncratic Volatility, and Investment Returns - Pan, Langxuan; Ye, Zixiang; Chen, Jiadong; Chen, Hanchuan (Transactions on Economics, Business and Management Research, 2024)
As informatization advances, online voting has become crucial in shareholder meetings, boosting participation from small and medium shareholders. This study examines Chinese companies listed in the A-share market from 2013 to 2022, showing a significant positive correlation between online voting by minority shareholders and idiosyncratic volatility in stock prices. Further analysis reveals that idiosyncratic volatility increases stock returns, and the interaction between online voting and idiosyncratic volatility strengthens the positive relationship between the two. The results remain valid after robustness tests, including core variables substitution, PSM testing, the instrumental variables method, exclusion of event-impacted samples, and handling missing data. Additionally, the findings from the heterogeneity analysis indicate that online voting participation will have a more significant increase in idiosyncratic volatility for firms with more advanced technology and higher levels of digital transformation. The significance of this study lies in enriching the research on the economic consequences of minority shareholders’ online voting and providing a foundation for differentiated corporate governance and policymaking.